Shear strength model for reinforced concrete columns with low transverse reinforcement ratios - Tran, Cao Thanh Ngoc (2014)
This paper introduces an equation developed based on the strut-and-tie analogy to predict the shear strength of reinforced concrete columns with low transverse reinforcement ratios. The validity and applicability of the proposed equation are evaluated by comparison with available experimental data. The proposed equation includes the contributions from concrete and transverse reinforcement through the truss action, and axial load through the strut action. A reinforced concrete column with a low transverse reinforcement ratio, commonly found in existing structures in Singapore and other parts of the world was tested to validate the assumptions made during the development of the proposed equation. The column specimen was tested to failure under the combination of a constant axial load of 0.30 f'cAg and quasi-static cyclic loadings to simulate earthquake actions. The analytical results revealed that the proposed equation is capable of predicting the shear strength of reinforced concrete columns with low transverse reinforcement ratios subjected to reversed cyclic loadings to a satisfactory level of accuracy.